Casa DeLuxe. Paradigmas do luxo arquitectonico - Samuel Pereira Pinto (2011)
The history of architectural styles can be looked upon based on the hitory of ceilings andlintels. This study sought to explore this angle of information in the period preceding the useof iron structures or reinforced concrete. It was decided to further reduce the scope of themasonry, leaving aside, for now, the wooden structures.The nineteenth century gave rise to an increasing need, in buildings, of upper floors withlarger free areas. This promoted some constructive solutions that we wanted to understandbetter.In the late nineteenth century, much construction was done with classical elements andprojective techniques that had not enjoyed a pre-determination of structural calculous like ithappens today. In these buildings, it was the architect who conceived the whole of thephysical form of the building, using his knowledges of geometry, proportion and architecturalhistory as the bases of his work. The architect-designer defined at the same time, structure andspatial confinement. And although mannerisms flourished, the project was based on a heritageof empirical knowledge about the stability of building, maintaining, in essence, the structuralelements in proportion with past cses of success.In this context, this work also uses some knowledge from civil engineering, that allows us tohave a different reading from the traditional architectural approach.Today we have detailed information on the stylistic evolution operated in buildings, butthere is fewer data or technical information on methods and construction systems used for thedesign and construction of roofs/ceilings and lintels of wider span.Today, some of this information resides only in a few specialized contractors and artisans,and in this context, it was fundamental the conversation held with master mason HumbertoSousa; master the archaic and pragmatic sense of the term.With the three buildings chosen as case stydies in this work, we tried to cover several typesof structures which design was not yet fully regulated by modern engineering. However, theAlfândega building, the most recent of the three, is also the one in which the typical approachof the architect would not be sufficient to determine the profile of the complex riveted iron beams.